EMPATI, PERSAHABATAN, DAN KECERDASAN ADVERSITAS PADA MAHASISWA YANG SEDANG SKRIPSI - Fauziah, Nailul (Faculty of Psychology, Diponegoro University, 2014)
AbstractThe aim of this study is to investigate the correlations between empathy, friendship, and adversity intelligence on undergraduate students who were in the stage of thesis writing (skripsi). Adversity intelligence is defined as person’s ability to overcome barriers and life challenges. The study sample comprised 74 ndergraduate students whom, at the time of study, were in the stage of thesis riting. They were approached using a purposive random sampling. Data were collected using Empathy scale, Friendships Scale, and Adversity Intelligence Scale. The results of simple regression analysis revealed a positive and significant orrelation between empathy, friendships, and adversity intelligence on subjects (r = 0,165; p = 0,001). Ability to develop empathy and to make new friends contributed to the development of students’ adversity intelligence. By developing social interaction, students learn to position themselves in dealing with problems; riendships creates intimacy, support, learning from previous mistakes and new experiences to overcome barriers, particularly on these final-yearstudents.